2016
DOI: 10.1128/jvi.00199-16
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons Regulate the Magnitude and Functionality of Mouse Polyomavirus-Specific CD8 T Cells in a Virus Strain-Dependent Manner

Abstract: Mouse polyomavirus (MPyV) is a ubiquitous persistent natural mouse pathogen. A glutamic acid (E)-to-glycine (G) difference IMPORTANCEIsolates of the human polyomavirus JC virus from patients with the frequently fatal demyelinating brain disease progressive multifocal leukoencephalopathy (PML) carry single amino acid substitutions in the domain of the VP1 capsid protein that binds the sialic acid moiety of glycoprotein/glycolipid receptors on host cells. These VP1 mutations may alter neural cell tropism or enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Virus-specific CD8 T cells control infections in the CNS via cytopathic and non-cytopathic effector mechanisms [ 70 ]. We previously reported that MuPyV infection was controlled in mice lacking TNF receptors or perforin and/or Fas as efficiently as in WT mice, and that IFN-γ and IFN-I inhibited MuPyV replication in vivo [ 32 , 33 , 71 ]. Likewise, IFN-γ and IFN-I inhibited JCPyV replication in established human glial cell lines and primary human glial cells [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Virus-specific CD8 T cells control infections in the CNS via cytopathic and non-cytopathic effector mechanisms [ 70 ]. We previously reported that MuPyV infection was controlled in mice lacking TNF receptors or perforin and/or Fas as efficiently as in WT mice, and that IFN-γ and IFN-I inhibited MuPyV replication in vivo [ 32 , 33 , 71 ]. Likewise, IFN-γ and IFN-I inhibited JCPyV replication in established human glial cell lines and primary human glial cells [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The key functions of type I IFN response involve activation and differentiation of DCs by promoting the expression of MHC molecules and various costimulatory molecules for the priming of T cells ( 34 , 60 ). Furthermore, type I interferons promote the cross-presentation of antigen to the CD8 + T cells ( 47 , 61 ) and are known to favor formation of memory CD8 + T cells ( 62 ). As CD8α + DCs are preferred APCs for cross-presentation, it is possible that the Inf.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse polyomavirus (MuPyV) and JCPyV have similar genomic and structural features and both establish persistent, asymptomatic infections in their natural hosts that are controlled by adaptive immunity (21,22). We reported that IFN-␥ and type I IFNs mediate viral control in the kidney and spleen (23,24). Here, we sought to determine whether type I, II, or III IFNs or STAT1 confer protection against MuPyV pathogenesis in the brain.…”
mentioning
confidence: 99%